Diversity of Pneumolysin and Pneumococcal Histidine Triad Protein D of Streptococcus pneumoniae Isolated from Invasive Diseases in Korean Children - Yun, Ki Wook (PLoS One, 2015)
Pneumolysin (Ply) and pneumococcal histidine triad protein D (PhtD) are candidate proteins for a next-generation pneumococcal vaccine. We aimed to analyze the genetic diversity and antigenic heterogeneity of Ply and PhtD for 173 pneumococci isolated from invasive diseases in Korean children. Allele was designated based on the variation of amino acid sequence. Antigenicity was predicted by the amino acid hydrophobicity of the region. There were seven and 39 allele types for the ply and phtD genes, respectively. The nucleotide sequence identity was 97.2%-99.9% for ply and 91.4%-98.0% for phtD gene. Only minor variations in hydrophobicity were noted among the antigenicity plots of Ply and PhtD. Overall, the allele types of the ply and phtD genes were remarkably homogeneous, and the antigenic diversity of the corresponding proteins was very limited. The Ply and PhtD could be useful antigens for universal pneumococcal vaccines.